10. FACTORS RELATED TO METABOLIC SYNDROME IN PEOPLE AGED 25-64 YEARS OLD IN THAI BINH PROVINCE (Vietnam Journal of Community Medicine, 2022)
Rationale: Metabolic syndrome (MetS) has been a public health issue in the spotlight recently. Themetabolic syndrome is increasing in the big cities and the red river delta provinces such as Thai Binh,where there is an incremental prevalence of MetS. Therefore, it is necessary to identify the situationof MetS engagement and its relevant factors.Research objective: Identifying some factors relating to metabolic syndrome in people aged 25 to64 in Thai Binh province.Research objects and methodology: The cross-sectional study was conducted on 1336 people aged25-64 years, aiming to identify the factors related to Metabolic Syndrome in people aged 25-64 in 6districts in Thai Binh province in 2019.Results: Some factors related to the Prevalence of Metabolic syndrome include: increase with age(OR = 1.08, p
Keywords: Metabolic Syndrome, 25-64 years old, Prevalence.